IMPLEMENTASI PRINSIP-PRINSIP GOOD GOVERNANCE DAN DAMPAKNYA TERHADAP KINERJA APARATUR PEMERINTAH DAERAH - Mahyuddin Mahyuddin; Sahri Sahri (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2022)
This study aims to analyze the implementation of good governance and its impact on the performance of local government apparatus. The data source in this study is using a questionnaire distributed to 32 Regional Device Organizations in West Nusa Tenggara Province which consists of Dinas, Agency, Office and Inspectorate. The research population was all state civil servants from the leadership element, head of field, staff in the general and service subsection, while the research sample was 96 respondents, namely: head of finance and planning subdivision, treasurer of expenditure and staff of finance and planning subdivision. The sampling technique of this study using the nonprobability sampling method with a purposive sampling approach, as well as the processing and analysis of all data in this study was carried out using the help of a computer device which was specifically carried out with the SPSS program version 22.0. The results of this study show that the implementation of the principles of good governance has a positive effect on the performance of the regional government apparatus of West Nusa Tenggara Province. By paying attention to other factors that can influence it, including: the principles of accountability, transparency, application of law, responsiveness, justice or equality, the ability of professional and responsible local government officials, the availability of adequate facilities and infrastructure, high responsibility of local government officials, the availability of adequate public information, and rules that are enforced fairly and evenly. Keywords: Good governance, performance, local government apparatus